Diagnostic method for the vibration syndrome with special reference to finger skin temperature and vibratory sense threshold - Niioka, Tadashi; Kojima, Yutaka; Kaji, Hiroshi; Saito, Kazuo (Scandinavian Journal of Work, Environment & Health, 1986)
The skin temperature and vibratory sense threshold of 34 chain-saw operators, ten of whom were diagnosed as suffering from vibration syndrome, and nine healthy students were measured before and immediately, 5, 10,and 15 min after 10 min of cold provocation of the left hand in water at a temperature of 10°C. Scattergrams of these parameters at the five points in time were drawn, and a boundary line for discrimination between the study groups was obtained at each of the five points in time. With the use of the boundary line for 5, 10, or 15 min after the provocation, it was possible to discriminate between the patients and the other subjects with more than 90 lifo accuracy. Considering the severe pain caused by the conventional5°C cold provocation test, the 10°C test can be recommendedfor the screening and diagnosis of vibration syndrome.
Keywords: chain saw; cold provocation test; cold provocation test at 10°C; correlation; diagnostic method; discriminant; finger; finger skin temperature; skin temperature; vibration syndrome; vibratory sense threshold